Les images du cheval attelé au travail dans les campagnes : réalités anatomique et morphologique et construction artistique à travers les enluminures (Europe, XIIe-XVIe siècle) - Floriana Bardoneschi (In Situ)
Images of harnessed horses at work in the country; anatomical and morphological realities and artistic construction in European illuminated manuscripts, twelfth to sixteenth centuries. Illuminated manuscripts offer an interesting source for looking at the way workhorses in the countryside are harnessed, during a given period. This focus raises questions about the scope of vision of these illuminations, which is both documentary and aesthetic. It allows us visualise the composition of the harness and how it was adapted to horses’ morphology, and to see the characteristics of workhorses used by peasants. This paper suggests some lines of enquiry which need to be pursued in other sources, in particular written records and archaeological material. This understanding of harnesses must also be completed by the study of the fabrication of harnesses and of the craftsmen active in this field.